To convert the quadratic function y = (x + 3)(2x - 5) to standard form y = ax^2 + bx + c, we need to first multiply the two binomials and then simplify the resulting equation.
Expanding the expression (x + 3)(2x - 5) gives:
y = 2x^2 - 5x + 6x - 15
y = 2x^2 + x - 15
Therefore, the values of a, b, and c are:
a = 2
b = 1
c = -15
So, the quadratic function in standard form is y = 2x^2 + x - 15.
Convert the following quadratic function to standard form y = ax^2 + bx + c and identify the values of a, b, and c.
y = (x + 3) (2x - 5)
a =
b =
c =
1 answer